The significance of De Ritis ratio in patients with radiation-recurrent prostate cancer undergoing salvage radical prostatectomy - Quhal, Fahad; Abufaraj, Mohammad; Janisch, Florian; Mori, Keiichiro; Lysenko, Ivan; Mostafaei, Hadi; D'Andrea, David; Mathieu, Romain; Enikeev, Dmitry V; Fajkovic, Harun; Heidenreich, Axel; Shariat, Shahrokh F (Arab journal of urology, 2020)
OBJECTIVE: To evaluate the clinical prognostic value of preoperative serum De Ritis ratio (DRR; aspartate aminotransferase/alanine aminotransferase) on postoperative survival outcomes in patients with radiation-recurrent prostate cancer (PCa) who underwent salvage radical prostatectomy (SRP). PATIENTS AND METHODS: A retrospective review was conducted of patients with radiation-recurrent PCa who underwent SRP in five tertiary referral centres from 2007 to 2015. An increased preoperative serum DRR was defined as ≥1.35. The association between DRR and postoperative outcomes was tested. Multivariate Cox analyses were performed to identify the independent predictors of biochemical recurrence (BCR), metastases-free survival (MFS), overall survival (OS), and cancer-specific survival (CSS). RESULTS: Overall 214 patients underwent SRP, of them 98 (45.8%) with a high serum DRR were included in the study. In a multivariate analysis high DRR was an independent predictor of BCR [hazard ratio (HR) 1.79, 95% confidence interval (CI) 1.16-2.78; P = 0.009]. No significant association was found between preoperative DRR and MFS (HR 1.32, 95% CI 0.53-3.30; P = 0.55), OS (HR 2.35, 95% CI 0.84-6.57; P = 0.10), and CSS (HR 3.36, 95% CI 0.65-17.35; P = 0.15). CONCLUSION: Increased preoperative serum DRR is associated with the development of BCR in patients with radiation-recurrent PCa who underwent SRP. DRR might serve as an early indicator of BCR, which may facilitate recognition of potential relapse and could translate into more intense follow-up and even salvage therapy in selected patients. ABBREVIATIONS: ADT: androgen-deprivation therapy; BCR, biochemical recurrence; BCRFS: BCR-free survival; CSS: cancer-specific survival; DRR: De Ritis ratio; HR: hazard ratio; MFS: metastasis-free survival; PCa: Prostate Cancer; OS: overall survival; PLND: pelvic lymph node dissection; (EB)RT: (external beam) radiotherapy; SRP: salvage radical prostatectomy.
Keywords: aspartate aminotransferase; SRP; alanine aminotransferase; prognostic; Biochemical recurrence